PROPOSED BUSINESS STRATEGY FOR CV ARTHA GUNA SANJAYA (TUSK BAG) IN CIMAHI (The Indonesian Journal of Business Administration, 2019)
Tusk Bag is a bag brand that has a product focusing on backpacks that have special containers for laptops (laptop backpacks). Tusk Bag was established in 2012 under the auspices of CV Artha Guna Sanjaya which is located on Jalan Raflesia No. 2 Blok C, Cihanjuang, Cibabat District, Cimahi City. Businesses in the field of fashion do have tremendous potential, including backpacks. At present, backpacks are a primary need for high school and college students. Tusk Bag has the advantage in its attractive design but has an affordable price. Therefore, Tusk Bag is able to develop until now. But problems arise in the sixth year. Tusk Bag began to experience a significant decline in sales from month to month. Not to mention the many competitors in the same industry. Therefore, the author conducted research and initiated a strategy for Tusk Bag so that it could increase its sales and compete with its competitors.The research began by analyzing the company's external and internal environment which affected the running of the Tusk Bag business. After that, from the analysis, create a segmentation for backpack products and determine the potential arena for Tusk Bag to enter. Then, using the AHP (Analytical Hierarchical Process) method determines the priority factor for Tusk Bag to develop. After that, formulating a strategy that is suitable for use by Tusk Bag in order to increase sales and compete with competitors.From the research that has been done, it was found that the design is still the main consideration of the buyer in choosing a backpack. However, from the results of the Importance-Performance Analysis (IPA) it was found that the brand is a factor that must be a top priority for Tusk Bag to be improved because from the survey results many have never heard of Tusk Bag before.Keywords: Backpack industry, sales declining problem, internal dan external environment analysis, diamond strategy consist of: arena, differentiator, vehicle, stage plan and economic logic.